Effect of retarded injection timing and EGR on performance, combustion and emission characteristics of a CRDi diesel engine fueled with WHDPE oil/diesel blends. (15th October 2020) - Kulandaivel, D.; Rahamathullah, I.G.; Sathiyagnanam, A.P.; Gopal, K.; Damodharan, D.; Melvin Victor, De Poures
Highlights: Oil extracted from waste high density polyethylene is utilized in diesel engine. Combined influence of EGR and retarded injection timing were employed. Characterization study were carried out to find the different compounds in the WHDPE oil. Abstract: In the present study, the effects of late injection timings and EGR rates on combustion, performance and emission characteristics were evaluated in a single cylinder diesel engine that utilizes oil extracted from waste HDPE which was blended with diesel at 30% by vol. (called as D70H30 blend). The experiments were conducted by delaying the injection timing viz., 23°bTDC, 18°bTDC, and 13°bTDC at various bmep. Later the effects of increasing EGR rates viz., 0%, 10% and 20% were studied at late injection timings at peak load condition. The results reveal that the peak cylinder pressure decreases and combustion duration gets shorter with delayed injection timing. For the same SoI timing escalating the EGR rates reduced the mean gas temperature which is reflected in lower HRR peaks. The BTE of the engine deteriorated by 4.6% when the injection timing is retarded from 23°bTDC to 13°bTDC and 3.2% when the EGR rate was escalated from 0% to 20% at peak load. NOx emission significantly decreased by 80% with retarded injection timing and further decreased with the application of EGR. On the other hand, smoke emission aggravated by 22% with retarded injection timing and 24.5% with maximum EGR addition. The HC and CO emissions followed the same trend of smoke emission. It can be concluded that, utilizing 30% waste HDPE oil blend with minimal modification like retarding injection timing and low EGR rates was beneficial in effectively reducing NOx emission with a slight drop in performance.